Isolation and characterization of alkaloids from Passiflora feotida for potential of antidepressant compounds - Hazrulrizawati, Abd Hamid; Mohd Hairul, Ab. Rahim; Aizi Nor Mazila, Ramli; Mashitah, Mohd Yusoff; Ahmad Faizal, Abdull Razis (2017)
The potential antimicrobial activity and acetylcholinesterase enzyme inhibition assay of water and methanol P. feotida extracts from fruits, leaves and stems were evaluated. Extracts from methanol fruits of P. feotida extract has found to be able to inhibit and resist the growth of pathogenic bacterial strains either Gram positive bacteria (Bacillus subtilis and Enterococcus faecalis) or Gram negative bacteria (Escherichia Coli and Pseudomonas aerogenosa). The identification of chemical constituents in P. feotida was done by UPLC-QTOF/MS and the results showed that this plant extract possessed a great number flavonoid compounds. With the presence of these compounds, it has contributed to the antimicrobial activity of P. feotida. Results of the present biological activity investigation further points to the potential of this plant species as a good source of new AChE inhibitors.